Modeling framework and coordination of DER and flexible loads for ancillary service provision - García, Jorge; Víquez, Juan M.; Incer, José; Escobar, Francisco; Valverde, Gustavo; Aristidou, Petros (My University, 2021)
Distributed energy resources and demand-response initiatives are expected to increase the flexibility of future power systems. This paper presents new models of individual photovoltaic systems, batteries, and thermostatically controlled loads that can be used to propose and validate new coordination schemes. Unlike previous works that focus on aggregate representations, these models make it possible to represent more accurately the capabilities and limitations of these resources. For demonstration purposes, the paper proposes a new coordination scheme that employs signals to individual units without having full information of their actual conditions. This low-cost scheme is able to steer the distributed units towards the desired operation. It is expected that mature versions of this type of coordinators will provide new tools and measures for system operators to face abnormal system conditions without high investment costs.
Keywords: Energy resources; Investments; Photovoltaic cells